Answer:
35.1
Step-by-step explanation:
6.75x5.2=35.1
Answer:
5/14
Step-by-step explanation:
Multiply.
(-5 × -1 × 4) / (7 × 8)
20/56
Simplify.
5/14
6.) y - (-3) = (1 - (-3))/(3 - 1) (x - 1)
y + 3 = (1 + 3)/2 (x - 1)
y + 3 = 4/2 (x - 1)
y + 3 = 2(x - 1) = 2x - 2
y = 2x - 2 - 3 = 2x - 5
y = 2x - 5
Answer:
189,2$
Step-by-step explanation:
220*0,86=189,2
14% = 14/100 = 0,14
1-0,14 = 0,86
price* factor between 0 and 1, 0 -> item is free, 1 -> full price
You want to put this in the form (x+b)^2 + c
To do this take half of the coefficient of b from the ordinal form which is 6/2=3 as use this as your new b
This give you (x+3)^2.
If you foil this out you get x^2 +6x +9 so you have added 9 to the original expression so now all you need to do is subtract 9 to keep things balanced
The final expression then is (x+3)^2 -9
<u> So c= -9</u>